2013
DOI: 10.7567/apex.6.103002
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Field Enhancement and Its Application in Spin Rectification

Abstract: A subwavelength antenna, which has the capability to enhance both the microwave electric and magnetic fields, is proposed for use in spintronic devices. The geometric resonance of the microwave electric and magnetic fields in the antenna are determined by spintronic techniques, and are in remarkable agreement with measurements taken using a vector network analyzer and simulations based on the finite-difference time-domain method. Our simulations predict that the performance of a spin dynamo may be improved by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Table 2 illustrates the comparison of the performances between the proposed PIFA and almost all the prior works which used antennas to study spintronics. The propagation distances are not given in [19‐21], while the enhanced electromagnetic field distributes a localized area of ~0.2 × 0.5 mm 2 . The work [22] is focused on studying the properties of new materials by monopole.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 illustrates the comparison of the performances between the proposed PIFA and almost all the prior works which used antennas to study spintronics. The propagation distances are not given in [19‐21], while the enhanced electromagnetic field distributes a localized area of ~0.2 × 0.5 mm 2 . The work [22] is focused on studying the properties of new materials by monopole.…”
Section: Resultsmentioning
confidence: 99%
“…Both the electric and magnetic fields exhibit significant enhancement with the help of the proposed PIFA. The enhanced field distributes across a relatively broad area, which is beneficial for the usage strip arrays in future works, such as the contrast experiments or other practical applications of SRE 19‐22 . The effects of changing L 2 on the performance of the PIFA are illustrated by the parametric studies shown in Figure 4, with the same plotting scale as in Figure 3.…”
Section: Antenna Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The spin rectification effect (SRE) and inverse spin Hall effect (ISHE) have attracted intense attention from researchers in many fields and led to a series of technological advances [9][10][11][12][13][14][15][16][17][18][19]. In recent years, some visionary physical scientists have noted that the SRE and ISHE may have potential in microwave power transfer [20][21][22][23][24][25], which aims at long-distance power transmission applications without the use of wire connections [26][27][28][29]. A more than 100 µV dc voltage could be genetared in one spintronic film strip 20 nm in thickness through the SRE and ISHE [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…To realize wireless coupling of the microwave spin excitation, elaborately designed microwave devices are essential for the SRE and ISHE. To date, coplanar waveguides [1,38], resonators [23,24,39], and probes [40,41] are the most commonly used devices in these studies, while antennas [20][21][22] are rarely reported. These devices offer many advantages in investigating spintronics.…”
Section: Introductionmentioning
confidence: 99%